A frightening thought: Neuronal activity enhances tumor growth - Thompson, Emily G (Cell Res, 2015)
Stem cells present in the adult brain are regulated by neuronal activity; malignant gliomas, which most likely originate from this population of cells, could also be regulated in this manner. A recent study by Venkatesh et al. published in Cell has identified Neuroligin-3 (NLGN3) as a mitogen promoting high-grade glioma growth.